Impact of comorbidities and personal characteristics on weather-related risk for community-acquired pneumonia - Brenner, Thomas; Link, Ann-Christine; Khan, Saeed Akhtar; Reudenbach, Christoph; Bendix, Joerg; Kutzinski, Max; Weckler, Barbara; Pott, Hendrik; Rupp, Jan; Witzenrath, Martin; Rohde, Gernot Gerhard Ulrich; Pletz, Mathias; et al. (Frontiers in climate, 2024)
Community-acquired pneumonia (CAP) is one of the most frequent causes of death among infectious diseases worldwide. There is a growing concern about weather impacts on CAP. However, no studies have examined the effects of comorbidities and personal characteristics alongside the twofold impact of weather conditions (meteorological and air quality) on CAP. Our study investigates how personal characteristics (age, sex, and BMI) and comorbidities (asthma, chronic heart disease, COPD, diabetes, heart insufficiency, smoking, and tumor) and care influence the twofold compound impact of weather on CAP admissions. We match medical data from a German multicentre cohort of 10,660 CAP patients with daily regional weather data, using logistic regressions to calculate the “Pneumonia Risk Increase Factor” (PRIF). This factor quantifies the heightened risk of CAP admissions due to weather conditions. We demonstrate that individuals with specific personal characteristics and those with comorbidities are more susceptible to weather impacts in the context of CAP than their counterparts. People with COPD have a PRIF of 5.28, followed by people in care (5.23) and people with a high BMI (4.02). Air pollutants, particularly CO and PM2.5, play a significant role in increasing CAP hospitalizations. For meteorological conditions, air pressure and lower temperatures, combined with air pollutants, lead to high PRIFs. Our findings emphasize the increased weather vulnerability of old, high BMI, and males and people with comorbidities. This provides invaluable information to support at-risk individuals through protective measures and provides healthcare providers as well as health policymakers with insights for resource planning before and during pneumonia-contributing weather conditions.
Gesehen am 23.01.2026